Association between oral contraceptives and cervical cancer: A retrospective case–control study based on the National Health and Nutrition Examination Survey - Guo, Chong; Zhan, Bo; Li, Meng-Yuan; Yue, Li; Zhang, Chao (Frontiers in Pharmacology, 2024)
Background: Cervical cancer was the fourth most common cancer among female globally with high incidence and high mortality among female in developing countries. This retrospective case-control study aimed to investigated the association between oral contraceptives and cervical cancer, which was a still insufficient evidence. Material and Methods: Multivariable logistic regression to examine the association between oral contraceptives and cervical cancer based on 7,496 females aged over 20 years from the National Health and Nutrition Examination Survey, conducted from 1999–2016 were employed. Results: Contraceptive use was positively associated with cervical cancer risk. In Model 1 (unadjusted), there was a 195% increased risk of cervical cancer among those who used the oral contraceptive (OR=2.27, 95%CI=1.39–3.98, P=0.002) compared to those who did not. In addition, The ORs for the exposed population were 1.74 (95%CI=1.05–3.08, P=0.041) and 1.93 (95%CI=1.16–3.44, P=0.017) in Model 2 (adjusted for age, race, BMI) and Model 3 (adjusted for education level, ratio of family income to poverty, drink status, smoking status, number of pregnancies, age at first sex, number of sexual partners, whether to receive the HPV vaccine in addition to Model 2), respectively. Furthermore, subgroup analyses stratified by age, smoking status, BMI, age at first sex, sex partners and whether to receive the HPV vaccine also revealed that oral contraceptives were significantly associated with cervical cancer. Conclusions: This study demonstrated that oral contraceptive use increased the risk of cervical cancer. In addition, the higher risk, including individuals with older than 45 years, having a high BMI (≥30 kg/m2), being current smokers, having more than 5 sexual partners, may contribute to the development at cervical cancer.